Sympathetic improvement of cancer vaccine efficacy - Else Marit Inderberg; Sébastien Wälchli (Taylor & Francis Group, 2020)
The link between stress, other psychological factors and response to cancer, or even the cancer incidence and metastasis, is well established. The inhibition of β-Adrenergic receptors (β-AR) using β-blockers was demonstrated to have an inhibitory effect on cancer recurrence. Direct effects on the stress-induced suppression of anti-tumor immune responses were also shown. In a recent issue of Cancer Immunology Research, Daher and colleagues studied the molecular mechanism behind this protective effect in the context of cancer vaccination. They provided evidence that the β-AR signaling affected the priming of naïve CD8 + T cells in their myeloma model, rather than effector CD8 + T cells which downregulated the expression of β-AR after activation and became insensitive to such signaling. Blocking the β-adrenergic signaling during vaccination led to increased expansion and effector functions of antigen-specific CD8 + T cells and reduced tumor growth. This has implications for the clinical use of β-blockers as adjuvants to enhance cancer vaccination and other types of immunotherapy.